2008
DOI: 10.1007/s00254-008-1390-1
|View full text |Cite
|
Sign up to set email alerts
|

Earth fissures triggered by groundwater withdrawal and coupled by geological structures in Jiangsu Province, China

Abstract: Earth fissures in Jiangsu Province, China have caused serious damages to properties, farmlands and infrastructures, and adversely affected the local or regional economic development. Under the geological and environmental background in Jiangsu Province, this paper presents the earth fissures caused by excessive groundwater withdrawal and coupled by distinctive geological structures, such as Ancient Yellow River Fault in Xuzhou karst area, and Ancient Yangtze River Course and bedrock hills in Suzhou, Wuxi and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…The mechanism leading to the generation of subsidence due to groundwater extraction and associated faulting is well-known [7,[36][37][38][39][40]. Nevertheless, the ability to calculate time, location, speed and magnitude of subsidence is limited due to the difficulty to determine the parameters that control the process [41,42].…”
Section: Identification Of Factors Contributing To Subsidence Hazardmentioning
confidence: 99%
“…The mechanism leading to the generation of subsidence due to groundwater extraction and associated faulting is well-known [7,[36][37][38][39][40]. Nevertheless, the ability to calculate time, location, speed and magnitude of subsidence is limited due to the difficulty to determine the parameters that control the process [41,42].…”
Section: Identification Of Factors Contributing To Subsidence Hazardmentioning
confidence: 99%
“…It has been clearly demonstrated that groundwater pumping creates horizontal displacements at local and regional scales (Burbey and Helm 1999). Tensional strain resulting from horizontal displacements can generate ground ruptures/ earth fissures with local damage to the surface and subsurface infrastructure (Wang et al 2009); hence, the development of a more realistic and accurate geomechanical model, which requires determination of the 3D deformation field accompanying the 3D flow field, is needed to develop more reliable predictions of both vertical and horizontal displacements. By incorporating horizontal deformation as a component of the total volume strain, which was assumed to be represented by only vertical strain in 1D models, the total volume strain is partitioned into three components (one vertical and two horizontal strain) and therefore the corresponding (1D and 3D) aquifer-system storage coefficients are potentially different.…”
Section: Introductionmentioning
confidence: 99%
“…Likely examples are recorded in the southwestern USA Jachens and Holzer, 1982;Holzer and Galloway, 2005], central Mexico [Pacheco et al, 2006;Carre on-Freyre et al, 2010, Iran [Ziaie et al, 2009;Mahmoudpour et al, 2013], Saudi Arabia [Bankher and Al-Harthia, 1999], and China [Li et al, 2000;Shi et al, 2007;Wang et al, 2009].…”
Section: Ground Rupturesmentioning
confidence: 99%